Stabilities and electronic properties of nanowires made of single atomic sulfur chains encapsulated in zigzag carbon nanotubes. (9th August 2018) - Li, Yuliang; Bai, Hongcun; Li, Linwei; Huang, Yuanhe
Abstract: Theoretical investigations are carried out on the recently synthesized one-dimensional nanowires made of atomic sulfur chains encapsulated in carbon nanotubes (called S@CNTs). Special attention is paid to stability, electronic property and transport properties of these combined nanowires. It is found that the encapsulation is exothermic when S@CNTs are built from the tubes with diameter larger than 6.4 Å. Thus the experimental results are energetically favorable since the diameters of the CNTs are about 6 Å in the obtained S@CNTs. The combined nanowires can be stabilized by van der Waals interaction between sulfur chain and tube as indicated from radial distribution function and reduced density gradient descriptions. All S@CNTs studied in this work exhibit metallic property with the partially filled bands. However, the conducting component and the pathway of charge carriers are various. For instance, only the sulfur chain is the conducting pathway for S@CNT(8, 0), while both the sulfur chain and tube are the conducting pathways for S@CNT(9, 0). This interesting feature was understood based on the band structures and crystal orbital analysis. The electronic transport properties of the systems are performed by investigating and analyzing the transmission spectra, current–voltage ( I–V ) curves and transmission eigenstate, which confirm that the sulfur chains can improve the electronic transport of CNTs. Moreover, the electrostatic interaction resulted from the charge transfer between the two components of S@CNTs should be favorable to the stability of the combined nanowires.